2017
DOI: 10.15252/msb.20167159
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent patterns of DNA copy number alterations in tumors reflect metabolic selection pressures

Abstract: Copy number alteration (CNA) profiling of human tumors has revealed recurrent patterns of DNA amplifications and deletions across diverse cancer types. These patterns are suggestive of conserved selection pressures during tumor evolution but cannot be fully explained by known oncogenes and tumor suppressor genes. Using a pan‐cancer analysis of CNA data from patient tumors and experimental systems, here we show that principal component analysis‐defined CNA signatures are predictive of glycolytic phenotypes, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 109 publications
4
53
1
Order By: Relevance
“…Although specific viral proteins (ie, EBNA1) have been identified to inhibit p53 function, 44 and thereby reduce genomic repair and ultimately increase CNAs, 45 the results of this study do not completely corroborate EBNA1 playing a primary role in CNA in EBV-infected tumor cells as CNA were more common in EBV-negative NPCs before the Bonferroni correction. However, an argument in favor of CNA playing a tumorigenic role in EBV-positive NPC is the association with worse survival.…”
Section: Role Of Viral Proteins In Copy-number Alterationcontrasting
confidence: 74%
“…Although specific viral proteins (ie, EBNA1) have been identified to inhibit p53 function, 44 and thereby reduce genomic repair and ultimately increase CNAs, 45 the results of this study do not completely corroborate EBNA1 playing a primary role in CNA in EBV-infected tumor cells as CNA were more common in EBV-negative NPCs before the Bonferroni correction. However, an argument in favor of CNA playing a tumorigenic role in EBV-positive NPC is the association with worse survival.…”
Section: Role Of Viral Proteins In Copy-number Alterationcontrasting
confidence: 74%
“…Other studies demonstrated that unicellular organisms, such as budding yeast or the pathogenic fungus Candida albicans , although maintaining a euploid state under stress-free conditions or for sexual reproduction, use aneuploidy as a readily available source of heritable variation for evolutionary adaptation to stressful environments (Chen et al, 2012; Kaya et al, 2015; Liu et al, 2015; Pavelka et al, 2010; Ryu et al, 2016; Selmecki et al, 2006; Sunshine et al, 2015; Yona et al, 2012). Accumulating evidence also suggests that specific aneuploid chromosome patterns may be selected during the evolution of cancer (Davoli et al, 2013; Graham et al, 2017). …”
Section: Physiological Consequences Of Aneuploidymentioning
confidence: 99%
“…Further, basal-like breast cancers share numerous molecular features including actionable targets with high-grade serous ovarian cancer (The Cancer Genome Atlas Research Network, 2012a). Copy number alteration patterns were found to be common in breast, ovarian, lung, and uterine samples and were predictive of glycolytic phenotypes (Graham et al, 2017). Squamous cell carcinomas from different anatomical sites share frequent alterations in TP53, PIK3CA, CDKN2A, SOX2, and CCND1 compared to other cancer phenotypes (Schwaederle et al, 2015).…”
Section: Introductionmentioning
confidence: 99%